Coagulation Attacks Over Networked Uavs: Concept, Challenges,and Research Aspects; International Journal of Advanced Trends in Computer Science and Engineering ( IJATCSE ); Vol. 8, No. 1.1, S I - Sharma V. Vishal; Kumar R. Ravinder; Srinivasan K. Kathiravan; Dzhayakodi Arachshiladzh D. N. K. Dushanta Nalin Kumara (2019, 2019)
Unmanned Aerial Vehicles (UAVs) have grasped an importantrole in the modern day networking. A lot of applica-tions arebeing developed using aerial vehicles as a pivot. These vehiclesprovide a vast range of support to modern day networks. Moderncomputing applications such as Urban Computing, Internet ofThings, Ubiquitous Computing, and the Internet for All havesought applications of UAVs to attain complex tasks. However,securing aerial vehicles in a network is not an easy task becauseof the difference in communication standards and range ofapplicability. Aerial nodes are prone to various types of attack ina network such as Sybil attack, wormhole attack, sinkhole attack,or impersonation attack. These attacks lead to a large number ofvulnerabilities causing fatal incidents. A new attack is introducedin this paper termed as “Coagulation Attack”. This term isderived from the clotting properties of fluids. This paperintroduces the concept, issues, challenges, and research aspects ofcoagulation attack. A simulation study is also presented thatshows the impact of such attacks over networked UAVs.